Evidence for increased in vivo sodium-potassium pump activity and potassium efflux in skeletal muscle of spontaneously hypertensive rats. - Syme, P; Dixon, R; Aronson, J; Grahame-Smith, D; Radda, G (1990)
We have used 87Rb nuclear magnetic resonance spectroscopy (NMR) to study in vivo rubidium kinetics in spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) controls, using rubidium as a marker for potassium. We gave 15 male, 13-week-old SHR, mean +/- s.d. blood pressure 180 +/- 10 mmHg, and 15 age-matched normotensive controls, mean blood pressure 120 +/- 9 mmHg, a daily dose of RbCl (2 mmol/kg intraperitoneally). We made repeated NMR measurements of skeletal muscle rubidium concentrations until steady state was reached. We then withdrew rubidium and made further measurements of rubidium concentrations, at intervals, for up to 1 week after the last injection. We also measured plasma and erythrocyte rubidium concentrations by flame atomic absorption spectroscopy at similar intervals after the withdrawal of rubidium. Rubidium concentrations rose at a faster rate in SHR skeletal muscle, but the steady-state muscle rubidium concentration was the same (45 mmol/l) in both SHR and WKY rats. There was also a threefold increase in the rate of rubidium efflux from both muscle and erythrocytes in SHR. These results are consistent with a marked increase in Na+,K(+)-ATPase activity and an increase in the rate of rubidium efflux in vivo in SHR. The increased rate of rubidium efflux in SHR could represent increased K+ efflux via calcium-activated K+ channels and/or result as part of cell volume regulation secondary to increased Na(+)-H+ antiporter activity.